Acta Universitatis Danubius. Œconomica, Vol. 10, No. 1: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
In this article we examine the influence of the leadership style on the resistance to change phenomenon, as well as how the degree of resistance to change differs in private organizations versus public ones. After analyzing the literature and conducting a survey in Romanian organizations we have concluded that the leadership style adopted by a top manager has an important impact on employees resistance to change. The research was designed to inform practitioners, researchers, managers and other interested persons about the influence of the leadership style on the resistance to change phenomenon, as well as how the phenomenon is manifested in different types of organizations. The main contribution of this paper is that in order to benefit of a lower degree of resistance to change from employees, the participative leadership style is recommended to be applied.